Higher Education Administrators’ Perceived Politics of Education Control on Educational Development of Tertiary Institutions in Bauchi State, Nigeria - Ibrahim, U.,; Edemenang,, C. E.,; Deba,, A. A.,; Adam, , M.; Abba,, I. S. D. (Kashere Journal of Education, 2021)
This paper focused on higher education administrators’ perceived impact of politics of control of education on educational development of tertiary institutions in Bauchi state, Nigeria. The study adopted qualitative research approach using case study design. Three specific objectives and three research questions were formulated to guide the study. The population consisted of senior higher education administrators from all the state’s tertiary institutions in the three geo-political zones of Bauchi state. The study had a sample of respondents drawn from the population using purposive sampling technique. The numbers that constituted the sample size were five and drawn from College of Education Azare, College for Legal and Islamic Studies Misau and College of Education Kangere within the three educational zone of Bauchi state. Area of the study is Bauchi state. Semi[1]structured interview, observation and document analysis were used for data collection. Data collected were analyzed using content and thematic analyses to answer the research questions of this study. Based on the findings, it was concluded that politics affects tertiary institutions positively via impact of control of education in Bauchi state. It was recommended among others that politics of education control should be done bearing in mind that, it should be intended to improved tertiary institution for sustainable development and not the other way round. It is hoped that the recommendations would serves as solutions towards the politics of education control on tertiary institutions for sustainable development in Bauchi state.